“La exclusión del tráfico de influencias como parte del delito de peculado y sus consecuencias jurídicas - Johana Natalí, Montenegro Brito (2020)
The crime of influence-peddling is a criminal offense committed by public servants in the exercise of their functions. It aims to archive an illegimate benefit of an economic or other nature by making favors or concessions abusing public office, for the benefit from third parties or from the server itself. This crime was found under the name of taking advantage of the charge to make favors or concessions. With the entry into force of the Integral Criminal Organic Code, influence-peddling that was part of the peculated crime was repealed. Application of the constitutional principle of “favorability” was one of the consequences; for this reason, this process was filed in favor of people who had a criminal process. People who were convicted of the crime of influence-peddling regained their freedom, every time the mentioned principle favors the application of the subsequent law, it will not be possible to condemn a person because a crime that was repealed by the Organic Comprehensive Criminal Code. To achieve the objectives of the project, the documentary bibliographic method was used, that permitted obtaining information related to the proposed topic, books legal doctrine and jurisprudence, which has permitted to support the theoretical framework. Likewise, field research has been carried out, which has made it possible to demonstrate the problem presented by the researcher.